Succession of the Program Freedom to Study Independent Campus Through Assistance in the Realization of School Waste Banks (BSS) as an Effort to Reduce the Distribution of Waste in the community - aliet aliet aliet (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
Community service, which is one of the university's chess dharma activities, is in conjunction with the program freedom to study independent campus (MBKM) aims to provide assistance in the realization of a school waste bank (BSS) for SDN I Kaliwadas Cirebon Regency in the post-pandemic as an effort to bring eco-literacy in the school environment. The method adopted in the implementation of this service is to use online and offline methods, in the form of technical and non-technical assistance for various needs for school waste bank installation equipment. Completion of mentoring activities includes socialization of waste processing mechanisms and school waste bank management. In this way, the existence of a school waste bank in the post-pandemic era has a fairly effective impact in presenting waste as a source of learning for students on the one hand, and presenting a strategy in suppressing the distribution of waste in the community, of course based on the populist economy on the other hand